Two cases of thyroid gland invasion by upper mediastinal carcinoma. (13th June 2019) - Yamazaki, Haruhiko; Iwasaki, Hiroyuki; Okubo, Yoichiro; Suganuma, Nobuyasu; Masudo, Katsuhiko; Nakayama, Hirotaka; Rino, Yasushi; Masuda, Munetaka
Summary: The objective this study is to report two cases of thyroid gland invasion by upper mediastinal carcinoma. Mediastinal tumors are uncommon and represent 3% of the tumors seen within the chest. In reports on mediastinal masses, the incidence of malignant lesions ranged from 25 to 49%. The thyroid gland can be directly invaded by surrounding organ cancers. We report these cases contrasting them to the case of a thyroid cancer with mediastinal lesions. Case 1 was a 73-year-old woman who was diagnosed with papillary thyroid carcinoma, and she underwent surgery and postoperative radioactive iodine. Case 2 was a 74-year-old man who was diagnosed with non-small-cell lung carcinoma, favor squamous cell carcinoma, and he underwent chemoradiotherapy. Case 3 was a 77-year-old man who was diagnosed a thymic carcinoma based on pathological findings and referred the patient to thoracic surgeons for surgical management. The images of the three cases were similar, and the differential diagnoses were difficult and required pathological examination. Primary thyroid carcinoma and invading carcinoma originating from the adjacent organs need to be distinguished because their prognoses and treatment strategies are different. It is important to properly diagnose them by images and pathological findings. Learning points: The thyroid gland in the anterior neck can be directly invaded by surrounding organ cancers. Primary thyroid carcinoma and invading carcinoma originating from the adjacent organs need to be distinguished because their prognoses and treatment strategies are different. It is important to properly diagnose by images and pathological findings.